Response of kale (Brassica alboglabra L.) to various planting media and application of liquid inorganic nutrition in DWC (deep water culture) hydroponic systems. Issue 1 (April 2020) - Yanti, C W B; Dermawan, R; Nafsi, N S; Rafiuddin,; Bahrun, A H; Mollah, A; Arafat, A
Abstract: Kale is one type of leaf vegetables that has a high nutritional content and is in demand by the community, hence has a high selling value. The purpose of this study was to investigate and determine the effect of liquid inorganic nutrients and various planting media in the hydroponic system on the growth and production of kale ( Brassica alboglabra L.) plants. The research was conducted from May to July 2017 in Manggala District, Makassar. The trial was set based on split plot design with two factors, liquid inorganic nutrition and various planting media. The main plot was nutrition which consisted of two types, namely AB-Mix nutrition and R-Mix nutrition. Subplot was planting medium with seven treatment combinations namely sand, burnt husk, cocopeat, combination of sand + burnt husk, sand + cocopeat, burnt husk + cocopeat, and sand + burnt husk + cocopeat. The results show that there was a significant interaction between the sand planting media and the R-Mix nutrition which produced the highest average of chlorophyll content (6.57 mg/g). The combination of burnt husk and cocopeat growing media gave yields that tended to be higher compared to other planting media. The R-Mix nutrient treatment gave a higher yield compared to other nutrients in the total chlorophyll observation (6.03 mg/g).